1996
DOI: 10.1097/00005344-199607000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Single-Blind Study of the Effects of Intravenous Dolasetron Mesylate Versus Ondansetron on Electrocardiographic Parameters in Normal Volunteers

Abstract: A single-blind, randomized, five-way cross-over, safety and tolerability trial was conducted to determine whether intravenous (i.v.) dolasetron mesylate at varying single doses induces changes in ECG intervals in healthy volunteers and to compare these changes with a single intravenous dose of ondansetron or placebo. Thirty healthy male volunteers received 1.2, 1.8, and 2.4 mg/kg i.v. dolasetron mesylate, 32 mg i.v. ondansetron, and placebo on 5 separate days. ECGs were recorded at intervals during the 24 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 20 publications
1
74
0
Order By: Relevance
“…13,[16][17][18][19][20] Palonosetron also appears to have an advantageous safety profile compared with ondansetron, granisetron, dolasetron, and tropisetron, which have been associated with electrocardiographic changes and arrhythmias, sometimes leading to the potentially fatal heart rhythm torsades de pointes. 13,14,[21][22][23][24] Palonosetron has been shown not to cause arrhythmias or symptomatic electrocardiographic changes. [25][26][27] The present study was designed to assess the efficacy and safety of two intravenous doses of palonosetron (10 and 20 µg/kg) in paediatric patients with cancer aged from new-born (full term; ≥37 weeks) to <17 years, scheduled to undergo moderately or highly emetogenic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…13,[16][17][18][19][20] Palonosetron also appears to have an advantageous safety profile compared with ondansetron, granisetron, dolasetron, and tropisetron, which have been associated with electrocardiographic changes and arrhythmias, sometimes leading to the potentially fatal heart rhythm torsades de pointes. 13,14,[21][22][23][24] Palonosetron has been shown not to cause arrhythmias or symptomatic electrocardiographic changes. [25][26][27] The present study was designed to assess the efficacy and safety of two intravenous doses of palonosetron (10 and 20 µg/kg) in paediatric patients with cancer aged from new-born (full term; ≥37 weeks) to <17 years, scheduled to undergo moderately or highly emetogenic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…12 Paradoxically, subsequent to the FDA warning on droperidol, ondansetron became adopted as a widely accepted, albeit far more costly substitute, despite the fact that it was also known to prolong the QT interval. 13,14 More recently, ondansetron and droperidol have been shown to have almost identical effects on the QT intervals of patients being treated for PONV in the recovery room. 3 The mechanism by which ondansetron prolongs QT is via blockade of the human ether-a-go-go-related gene (HERG) potassium channel in the myocardium, leading to disruption of the rapid delayed rectifier potassium current (I kr ).…”
Section: Discussionmentioning
confidence: 99%
“…Htr3 antagonists, which are widely used as antiemetics, have been reported to prolong the QT intervals and to be related to tosades de pointes in high concentrations. [9][10][11][12] This finding suggests that serotonin and Htr3 might be related to cardiac repolarization. Recently, it was reported that mouse cardiac tissue contained mRNA for Htr3.…”
Section: Clinical Implicationmentioning
confidence: 99%